2019
DOI: 10.7150/ijms.34629
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reaction profiles of hemorrhagic adverse reactions caused by direct oral anticoagulants analyzed using the Food and Drug Administration Adverse Event Reporting System (FAERS) database and the Japanese Adverse Drug Event Report (JADER) database

Abstract: Direct oral anticoagulants (DOACs) are used in anticoagulant therapy. The purpose of this study was to evaluate the association of DOAC-induced gastrointestinal (GI) and nervous system hemorrhage using the FDA's Adverse Event Reporting System (FAERS) database and the Japanese Adverse Drug Event Report (JADER) database.We identified and analyzed the reports of hemorrhagic reactions between 2004 and 2016 from the FAERS and JADER databases, and calculated the adjusted reported odds ratio (ROR) using the multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…A cohort study has shown that the risk for bleeding, especially gastrointestinal bleeding, inherently increases with rising age [60], it may then be potentiated by antithrombotics. In this respect, higher numbers of ADR reports with regard to gastrointestinal and nervous system haemorrhages associated with direct oral anticoagulants have been seen in patients aged 60 years or older compared to younger patients in a study performed in two large ADR databases from USA and Japan [61]. Haemorrhages were the cause of death reported most often in the Swedish study of fatal ADR reports [11].…”
Section: Discussionmentioning
confidence: 98%
“…A cohort study has shown that the risk for bleeding, especially gastrointestinal bleeding, inherently increases with rising age [60], it may then be potentiated by antithrombotics. In this respect, higher numbers of ADR reports with regard to gastrointestinal and nervous system haemorrhages associated with direct oral anticoagulants have been seen in patients aged 60 years or older compared to younger patients in a study performed in two large ADR databases from USA and Japan [61]. Haemorrhages were the cause of death reported most often in the Swedish study of fatal ADR reports [11].…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that there is not one single measure of effect that is superior to the others 8 , 51 , 52 . Our study utilized reporting odds ratios to characterize the frequency of liver injury reports as it is a straightforward and frequently used measure for the analysis of FAERS data 45 , 53 , 54 , 55 , 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…There are no head-to-head randomized clinical trials to investigate the hemorrhage risk of different NOACs. Up to now, several studies have been conducted to assess the bleeding risk of NOACs using some spontaneous reporting systems (14,(16)(17).…”
Section: Discussionmentioning
confidence: 99%